Non-user - Selwa Sweidan; Karlynne Ejercito (Internet Policy Review, 2022)
A "non-user," as the name suggests, refers to an individual who does not use a given product or system. Critical work on non-use elaborates a range of applications for the term we consider here. The variations of non-use under discussion encompass both voluntary and involuntary cases of non-use.
Keywords: 300; User behaviour; Digital uses; User experience; User consent; User rights; Non-user